2016
DOI: 10.1007/s13577-015-0130-6
|View full text |Cite
|
Sign up to set email alerts
|

The advantages of incorporating liquid-based cytology (TACAS™) in mass screening for cervical cancer

Abstract: We incorporated liquid-based cytology (LBC) in population-based screening for cervical cancer. The usefulness of using LBC in mass screening for cervical cancer was examined. From 2009 to 2014, 157,061 individuals underwent mass screening for cervical cancer in Aomori Prefecture. From 2009 to 2011, cells were collected from 82,218 individuals and the specimens were conventionally prepared (CP). From 2012 to 2014, cells were collected from 74,843 individuals and the specimens were prepared using LBC (TACAS™). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…A study conducted in Japan examined the advantages of LBC over conventional PAP smear in mass screening for cervical cancer. They reported that the detection rate of ASC-US and more severe lesions using LBC was 1.44%, whereas it was 1.13% using conventional PAP smear, hence a 1.3-fold higher detection rate when using LBC [7]. Our results showed comparable findings.…”
Section: Lbc Liquid-based Cytologysupporting
confidence: 73%
“…A study conducted in Japan examined the advantages of LBC over conventional PAP smear in mass screening for cervical cancer. They reported that the detection rate of ASC-US and more severe lesions using LBC was 1.44%, whereas it was 1.13% using conventional PAP smear, hence a 1.3-fold higher detection rate when using LBC [7]. Our results showed comparable findings.…”
Section: Lbc Liquid-based Cytologysupporting
confidence: 73%